Prevalence of cryptococcal antigen (CrAg) among HIV-positive patients in Eswatini, 2014–2015 - Samson M. Haumba; Mitsuru Toda; Rossana Jeffries; Peter Ehrenkranz; Munyaradzi Pasipamire; Trong Ao; Nomthandazo Lukhele; Sikhathele Mazibuko; Mandzisi Mkhontfo; Rachel M. Smith; Tom Chiller (African Journal of Laboratory Medicine, 2020)
Background: Cryptococcal meningitis is a leading cause of death amongst people living with HIV. However, routine cryptococcal antigen (CrAg) screening was not in the national guidelines in Eswatini.